2020
DOI: 10.1103/physrevfluids.5.104201
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial instability of thin films in soft microfluidic configurations actuated by electro-osmotic flow

Abstract: We analyze the interfacial instability of a thin film confined between a rigid surface and a pre-stretched elastic sheet, triggered by non-uniform electro-osmotic flow. We derive a nonlinear viscous−elastic equation governing the deformation of the elastic sheet, describing the balance between viscous resistance, the dielectric and electro-osmotic effects, and the restoring effect of elasticity. Our theoretical analysis, validated by numerical simulations, shows several distinct modes of instability depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…On the other hand, a computational study by de Rutte et al [221] on electroosmotic flow in a compliant microchannel concluded that a narrow and wide flow conduit can collapse over a range of imposed electric field strengths, and the effect is "exacerbated for soft materials such as PDMS." Boyko et al [222,223] expounded on this idea, showing that "above a certain electric field threshold, negative gauge pressure induced by electro-osmotic flow causes the collapse of its elastic wall." They experimentally demonstrated this novel type of fluid-structure instability and showed that an electroosmotic fluid-structure interaction parameter β ∝ B/(k w Lh 3 0 /η 0 ) (recall section 3.6) controls the (in)stability in a 2D Cartesian configuration as in figure 7(a).…”
Section: Electrohydrodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a computational study by de Rutte et al [221] on electroosmotic flow in a compliant microchannel concluded that a narrow and wide flow conduit can collapse over a range of imposed electric field strengths, and the effect is "exacerbated for soft materials such as PDMS." Boyko et al [222,223] expounded on this idea, showing that "above a certain electric field threshold, negative gauge pressure induced by electro-osmotic flow causes the collapse of its elastic wall." They experimentally demonstrated this novel type of fluid-structure instability and showed that an electroosmotic fluid-structure interaction parameter β ∝ B/(k w Lh 3 0 /η 0 ) (recall section 3.6) controls the (in)stability in a 2D Cartesian configuration as in figure 7(a).…”
Section: Electrohydrodynamicsmentioning
confidence: 99%
“…To highlight the novel features of these electroosmotic flows in soft hydraulic conduits, it is instructive to consider the unsteady lubrication model from [223]. In this case, (60) becomes…”
Section: Electrohydrodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another emerging application is in the field of reconfigurable microfluidics (Paratore et al 2022), where thin liquid films could be used to dynamically deform the surface of a thin membrane of a microfluidic chip, in order to control its functionality in real time. The film dynamics in such applications can be described by the same set of equations, whether a liquid-fluid or a liquid-membrane interface is used (Hosoi, Mahadevan & Peeling 2004;Kodio, Griffiths & Vella 2017;Boyko et al 2019Boyko et al , 2020. The ability to design such devices, predict their performance and understand their fundamental limitations, would greatly benefit from a theoretical framework that allows their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The film dynamics in such applications can be described by the same set of equations, whether a liquid-fluid or a liquid-membrane interface is used (Hosoi, Mahadevan & Peeling 2004; Kodio, Griffiths & Vella 2017; Boyko et al. 2019, 2020). The ability to design such devices, predict their performance and understand their fundamental limitations, would greatly benefit from a theoretical framework that allows their analysis.…”
Section: Introductionmentioning
confidence: 99%